Synthesis and characterization of novel scaffold for bone tissue engineering based on Whartons´s jelly - Martinez, Cristian (2017)
A composite is a material made of more than one component, and the bond between the components is on a scale larger than the atomic scale. The objective of the present study was to synthesize and perform the structural characterization and biological evaluation of a new biocomposite (BCO) based on a novel combination of an organic and an inorganic phase, for bone tissue engineering applications. The organic phase consisted of Wharton´s Jelly (WJ), which was obtained from embryonic tissue following a protocol developed by our laboratory. The inorganic phase consisted of bioceramic particles (BC), produced by sintering hydroxyapatite (HA) with β- tricalcium phosphate (β-TCP), and bioactive glass particles (BG). Each phase of the BCO was fully characterized by SEM, EDS, XRD and FTIR. Biocompatibility was evaluated in vivo in the tibiae of Wistar rats (n=40). Histological evaluation was performed at 0, 1, 7, 14, 30 and 60 days. XRD showed the phases corresponding to HA and β-TCP, whereas diffractogram of BG showed it to have an amorphous structure. EDS showed mainly Si and Na, Ca, P in BG, and Ca and P in HA and β-TCP. FTIR identified bonds between the organic and inorganic phases. From a mechanical viewpoint, the composite showed high flexural strength of 40.3±0.8MPa. The synthesized BCO exhibited adequate biocompatibility as shown by formation of lamellar type bone linked by BG and BC particles. The biomaterial presented here showed excellent mechanical and biocompatibility properties for its potential clinical use.